PENGARUH TERAPI KETAWA TERHADAP TEKANAN DARAH LANSIA HIPERTENSI DI WILAYAH KERJA PUSKESMAS PEMBANTU DESA KEPENUHAN RAYA - Gustina, Sri; Herma Yesti; Andriana (Maternity and Neonatal : Jurnal Kebidanan, 2024)
Hypertension is a disease caused by a condition when blood pressure at 130/80 mmHg or more for which the cause is not known with certainty. The elderly with hypertension need attention, especially in reducing blood pressure. Nonpharmacological action, laughter therapy can lower blood pressure. Laughter can lower levels of certain hormones linked to the stress response: cortisol, epinephrine and dopac. Laughter relieves stress, depression, anxiety, sadness, anger and can trigger the release of endorphins, thereby relieving pain. This research is a pre-experimental study conducted with a sample of 13 respondents. The results of this study indicate that the average decrease in blood pressure in elderly people with hypertension before and after being given laughter therapy is 15.385 mmHg for systolic blood pressure and 7.69 for diastolic blood pressure. Asymp.Sig value is 0.043 which means <0.05 Ha is accepted and Ho is rejected. There is an effect of laughter therapy on blood pressure in the elderly with hypertension in the working area of the Kepuhan Raya village auxiliary health center in 2023.